1980
DOI: 10.1017/s0020743800031238
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of Egypt's Militant Islamic Groups: Methodological Note and Preliminary Findings

Abstract: Iran's Islamic Revolution seems to have taken the world by surprise. The Western mass media have subsequently been alarming their readers with warnings of Islamic “revival,” “resurgence,” “rumble,” and “anger.” Strategists and political practitioners have joined in – invariably using the same or more academic-sounding jargon, such as the “arc of trouble” or the “crescent of crisis.” The area referred to stretches from Morocco to Indonesia, where nearly 800 million Muslims live and in which some of the world's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(38 citation statements)
references
References 7 publications
0
37
0
1
Order By: Relevance
“…What started as an early confrontation between the two civilizations led to the different schools of thought being embedded in the various forms of elitist and popular revivalist movements (Feldman 2008;Hunter 1998;Zubaida 1993;Anderson 1987;Owen 2004;Ibrahim 1980 shari'a and pluralist institutions (Ramadan 2009: 148).…”
Section: Attitudes Toward Democracy In the Arab Worldmentioning
confidence: 99%
“…What started as an early confrontation between the two civilizations led to the different schools of thought being embedded in the various forms of elitist and popular revivalist movements (Feldman 2008;Hunter 1998;Zubaida 1993;Anderson 1987;Owen 2004;Ibrahim 1980 shari'a and pluralist institutions (Ramadan 2009: 148).…”
Section: Attitudes Toward Democracy In the Arab Worldmentioning
confidence: 99%
“…Moghadam (1993) also stresses that fundamentalist preferences are not a function of class among women. Egyptian sociologist Saad Eddin Ibrahim (1980) has shown that Islamic extremists tend to be well-educated, upwardly-mobile young men, not the stereotypical slum dweller. Members of the Muslim Brotherhood across the Islamic world are very often doctors, lawyers, and engineers.…”
mentioning
confidence: 99%
“…Ansari, Cinnirella, Rogers, Loewenthal, and Lewis (2006) examined attitudes (potentially extreme) among British Muslims. Ibrahim (1980) conducted interviews with two groups of the terrorists who were involved in bloody confrontations with the regime in Egypt resulting in casualties. Other studies involved interviews with individuals who committed terrorist acts (Bakker, 2006;Post, Merari, & Ganor, 2008;Stern, 1999Stern, , 2003.…”
Section: Introductionmentioning
confidence: 99%